2017
DOI: 10.1210/js.2017-00055
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Disease, Women, and Aldosterone: Finding a Link in the Jackson Heart Study

Abstract: Context:Fatty liver disease is one of the most common forms of chronic liver disease. The renin-angiotensin-aldosterone system has been implicated in the pathogenesis of fatty liver.Objective:Determine the relationship between fatty liver and aldosterone in a large cohort study.Design:Community-based, observational cohort study of African Americans.Setting:The original Jackson Heart Study cohort enrolled African American participants from the Jackson, Mississippi, metropolitan area in Hinds, Madison, and Ranki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the liver, the aldosterone level is increased in liver fibrosis [ 22 ] and can increase the levels of liver fat consistently enough to be used as a predictor of liver fat levels [ 23 ]. Aldosterone is also involved in the pathogenesis of the fatty liver disease [ 24 ] and in the pathogenesis of obesity and overweight [ 25 , 26 ]. Fat metabolism and oxidation were also inhibited in our dataset ( Figure 4 ) and reduction of the fat oxidation category is likely partially controlled by the inhibited and downregulated HNF4A—hepatocyte nuclear factor 4 alpha transcription factor ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, the aldosterone level is increased in liver fibrosis [ 22 ] and can increase the levels of liver fat consistently enough to be used as a predictor of liver fat levels [ 23 ]. Aldosterone is also involved in the pathogenesis of the fatty liver disease [ 24 ] and in the pathogenesis of obesity and overweight [ 25 , 26 ]. Fat metabolism and oxidation were also inhibited in our dataset ( Figure 4 ) and reduction of the fat oxidation category is likely partially controlled by the inhibited and downregulated HNF4A—hepatocyte nuclear factor 4 alpha transcription factor ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence from animal models suggests that the use of MR antagonists, such as eplerenone, study showed an association between increased aldosterone and fatty liver in black women, demonstrating that perturbations in the renin-angiotensin-aldosterone system likely affect hepatic steatosis. 15 Regardless of mechanism, this pilot study provides preliminary data suggesting that the pathophysiological benefits of MR antagonism seen in animal models may not translate directly into humans.…”
Section: Discussionmentioning
confidence: 91%
“…The relationship between liver attenuation and aldosterone has previously been investigated in the JHS ( Kumar et al, 2017 ). Investigators identified a negative association between aldosterone and liver attenuation which was significant only among women.…”
Section: Discussionmentioning
confidence: 99%